An empirical study on the effectiveness of mall method in enhancing EFL students’ listening comprehension - Guofang Xiong; Wendy Hiew (Global Academic Excellence, 2024)
The advent of Mobile-Assisted Language Learning (MALL) has revolutionized English as a Foreign Language (EFL) education by providing learners with unprecedented access to language learning resources anytime and anywhere. Listening is often considered one of the most challenging skills to master in language acquisition. While previous research has shown the effectiveness of the MALL method in areas such as writing and reading, few empirical studies have focused on its application in EFL listening classes. This empirical study adopted a mixed-method approach, collecting quantitative data from pre- and post-tests and qualitative data from learners’ journals, to investigate the effectiveness of the MALL method in enhancing EFL learners’ listening comprehension and learners’ attitude toward MALL in their listening practice. Data were collected and analyzed using SPSS. The results indicated that the MALL method is effective in improving EFL listening comprehension and allows learners for the adjustment of content and pace, facilitating personalized and effective learning experiences. This study aims to provide insights for incorporating MALL in EFL listening studies and improving listening efficiency.